Dynamics of Demand for Rainfall Index Insurance : Evidence from a Commercial Product in India - Stein, Daniel (World Bank Group, Washington, DC, 2014)
This paper analyzes the dynamic nature of rainfall insurance purchasing decisions, specifically looking at whether and why receiving an insurance payout induces a greater chance of purchasing insurance again the next year. This analysis uses customer data from the Indian micro-finance institution BASIX, and finds that receiving an insurance payout is associated with a 9 to 22 percentage points increased probability of purchasing insurance the following year. This affect appears to be driven by behavioral effects of receiving a payout, and cannot be explained by trust, learning, or direct effects of weather. Overall, low repurchasing rates even after payouts suggest that current rainfall index insurance products are likely to continue struggling to achieve significant sales at market prices.